(untitled) (Revista de Ciências Agroveterinárias, 2015)
Canopy management is an important tool for adjusting the balance between leaf area and yield, though its effect on grape quality depends on the type of management, the time at which measurements are taken and the soil and climate conditions of the vineyard. The aim of this study was to evaluate lateral shoot removal as it affects the physo-chemical qualities of grape bunches grown at high altitude at the moment in which the berries were changing color. The experiment, conducted in a commercial vineyard in Sao Joaquim, SC (28°17‘S; 49°55’; 1,150 m altitude), tested Sangiovese grapes from 2007 to 2008, and Tempranillo grapes from 2008 to 2009. These varietals were grafted onto Paulsen 1103 and placed on a trelace training system, double-spaced at 3.0 m x 1.5 m. Canopy management controls were applied without removing side shoots in order to maintain a leaf-area of 2.50 m2 per kg of Sangiovese cultivars and 3.54 m2 per kg of Tempranillo cultivars. In the Sangiovese cultivar for the 2006/07 season, the cluster and rachis had a higher relative mass in plants in which the leaf area was not reduced, while an increase in the content of soluble solids and easily extractable anthocyanins in the plants with reduced leaf areas was observed, increasing the quality of early ripening Sangiovese grapes. No significant difference in physical-chemical qualities was observed in the Tempranillo cultivar when reducing the canopy leaf area in the early ripening berries for both crop seasons.